Perfil dos idosos submetidos à cirurgia oftalmológica e as implicações da hipertensão arterial: um estudo no Hospital Universitário Bettina Ferro de Souza - ESPIRITO SANTO, Evelin Lorena Sousa do (2019)
The aging population is reflected in the increase of chronic degenerative diseases associated with senescence, as well as more recently the increase in surgical procedures. This study aimed to verify the profile and incidence of hypertension (HBP) in elderly patients undergoing eye surgery in HUBFS. It is a cross-sectional, prospective, quantitative data analysis, which are collected from the questionnaire used as a tool collection. Verification of BP followed the procedures recommended in the VI Brazilian Guidelines on Hypertension. The collection period was from July to December 2010. Of the 32 elderly sample, the majority were female (53.1%), mean age 68.3 years, mulato (56.3%) from the metropolitan area of Belém (65.6%), education up to primary incomplete or complete ( 81.3%). Do not perform paid work (81.3%) have household incomes of up to three minimum wages (87.5%). BMI presented no risk for cardiovascular disease (59.4%), did not practice physical activity (62.5%), are not heavy drinkers (84.4%) or smokers (93.8%). Some have undergone surgery at least once or twice in your life (62.5%). After classification of blood pressure levels, we identified 81.3% of elderly hypertensive patients. There was no statistically significant relationship between hypertension and the variables: age, race, education, income, physical activity, alcohol consumption, smoking and other risk factors such as heart disease, lipid disorders, anxiety and diabetes. Statistically significant relationships were found between hypertension and gender, BMI, waist circumference (WC) and surgical experience. Evaluated by Student's t test for independent samples, we found that in males the final average SBP was significantly higher than females (p = 0.01). Analyzed using Pearson's correlation (r), WC and BMI showed moderate positive correlation (r = 0,753, p = 0.00).Among the variables, BMI and SBP (r = 0,403, p = 0.022) and DBP (r = 0,457, p = 0.009) and WC with SBP (r = 0,409, p = 0.020) and DBP (r = 0,391, p = 0027), there was a weak positive correlation. The result of simple linear regression analysis of BMI and WC with hypertension was positive and continuous, with both SBP (coefficient β1 = 1489) and DBP (coefficient β1 = 1155) with BMI, and SBP ( coefficient β1 = 0.498) and DBP (coefficient β1 = 0325) with WC, indicating that for every one-unit increase in BMI, SBP increase by 1,489 mmHg and DBP mmHg increase in 1155, and that for each increase of 1 cm in WC to increase by 0,498 mmHg SBP and DBP increase in 0.325mmHg. The mean values and standard deviation of SBP and DBP from experience of the surgical sample revealed statistically significant results, and among the four groups the mean difference between the SBP (p = 0.02) and DBP (p = 0.01) of the elderly with a two or surgical experience was greater than in those with three or four surgical experience (p = 0.02), the significance level of 5%. Therefore, identify the profile of elderly patients undergoing ophthalmic surgery was important to understand the demands of this type of patient and influence that hypertension has on them, revealing the need for greater attention to supportive care provided.